Penerapan Metode Bercerita untuk Meningkatkan Kreativitas pada Siswa TK Kelompok B - Ratih Widyastuti Permatasari (Universitas Trunojoyo Madura, 2014)
Childhood, especially at an early age is often reffered to as the golden age the sensitive period in receiving various stimulation. Early childhood education for the formal education of kindergarten. However, in reality the conditions are too oriented academic kindergarten education where learning is more emphasis on writing, arithmetic and reading the familiar linear thinking, logical, orderly and convergent, divergent thinking so unaccustomed. Whereas divergent thinking pattern is a pattern of thinking that trying to find alternative thinking (creative) to obtain a wide range of solutions to problems. Creativity takes the child in the process of life, especially in the resolution of difficulties, the discovery of new works or new solutions. Based on the problems that the researchers used storytelling as an intervention method that is used to increase the creativity of children. The subjects were students in kindergarten group B 5-6 years old. Evaluation from of pre-test and post-test tell the story of an image. The difference in scores will be analyzed using statistical techniques paired sample t test.result of statistical analysis, know t =-2,990 and p =0,015, in this case p 0,05 indicates a significant difference that there is an increase in the score before the post-intervention. The average score before intervention was 14,10 and the average score after the intervention was 18,30, so that the increase is 4,20. Thus, we can conclude that storytelling can increase a child’s creativity TK group B.